SPECIFIC CRITERIA FOR EVALUATING AND PREDICTING THE HYDRODYNAMIC TRAINING OF HIGHLY QUALIFIED PARALYMPIC SWIMMERS - Vinokourov L.V. ,; Lebedeva A.L., (Theory and Practice of Physical Culture, 2023)
Objective of the study was the empirical identification of signs-indicators for the formation of specific criteria for assessing the effectiveness of hydrodynamic training (preparedness) of a Paralympic swimmer. Methods and structure of the study. The study was carried out in 2022 in the sport of the blind and in the sport of persons with a lesion of the musculoskeletal system as part of the scientific and methodological support of the Russian national team in Paralympic swimming. 23 coaches took part (14 sports of people with a lesion of the musculoskeletal system, 9 sports of the blind). We used the method of expert survey of leading coaches of high-class paraswimmers (Master of Sports, Master of Sports of International Class, Honored Master of Sports) using a questionnaire. Questionnaire items associated with specific signs-indicators were masked by items that included information about the signs-indicators of hydrodynamic training, characteristic of all paraswimmers (regardless of the specifics of nosological features), as well as for healthy athletes. Results and conclusions. To solve the problems of special technical and tactical training, control and forecasting of hydrodynamic training of a Paralympic swimmer, depending on the nosological features, specific criteria for assessing the hydrodynamic characteristics of a paraswimmer have been formed. It is shown that in the sport of persons with lesions of the musculoskeletal system (LMS) the criterion "individual propulsion ability" should be considered as a specific one, and in the sport of the blind - the criterion "orientation at a swimming distance". It has been established that each of the evaluation criteria is meaningfully disclosed by means of signs-indicators, reflecting a close relationship with nosological features specific for paraswimmers of one of these sports.